Molecular characterization and genetic variability of Toxocara vitulorum from naturally infected buffalo calves for the first time in Bangladesh - Hiranmoy Biswas; Nurnabi Ahmed; Babul Chandra Roy; Mohammad Manjurul Hasan; MD Khalilur Rahman; Md. Hasanuzzaman Talukder (Parasitology, 2024)
Toxocara vitulorum is one of the deadliest parasite of buffalo calves in Bangladesh. This study was conducted to explore genetic variability within and among the T. vitulorum populations in buffalo calves of Bangladesh. Genomic DNA was extracted, ITS2, COX1 and NAD1 gene were amplified and sequenced. Distinct 29 ITS2, 21 unique NAD1 and 24 COX1 genotypes were detected among the T. vitulorum of different geographic regions. These three gene genotypes similarities ranged from 97 to 99%, when these were compared to best hit scoring T. vitulorum sequences retrieved from GenBank. A total of 12 and 6 unique haplotypes were detected for COX1 and NAD1 gene sequences. The average nucleotide and haplotype diversity for COX1 and NAD1 were 0.0931 & 0.89493 and 0.00658 & 0.77895 respectively and the recorded values were more dispersed than previously published values. The pairwise Nst values ranged from −0.050 to 0.602 and Fst from −0.050 to 0.600 between all the T. vitulorum genotypes indicated huge genetic differentiation which were reportedly higher than other published reports Fst values. This is the first report of T. vitulorum on the basis of COX1 gene in Bangladesh. The study findings will be helpful for further extensive epidemiological studies regarding anthelmintic resistance, control and prevention of T. vitulorum infection in buffalo calves.